MacDowell Colony (Peterborough, N.H.) records - MacDowell Colony (Peterborough, N.H.); Edward MacDowell Association
Correspondence, admission application records, minutes of meetings, reports, legal and financial papers, scrapbooks, and miscellany chiefly concerning the administration and operation of the MacDowell arts colony. Includes material relating to the colony's board of directors and committees, as well as the various artists, writers, and musicians who were chosen as residents. Persons prominent in the collection, either as correspondents or officers of the colony, include Hervey Allen, Marie Brodeur, Alexander Calder, Padraic and Mary Colum, Aaron Copland, Parker and Louise Dutton Fillmore, Max Frankel, Chaim Gross, Thomas Shaw Hale, DuBose Heyward, Lewis Montefiore Isaacs, George M. Kendall, Marianne Moore, Tillie Olsen, Charles H. Studin, James Johnson Sweeney, Louise Talma, Jean Starr Untermeyer, and Thornton Wilder. Also includes letters (1936-1938) to Hermann Hagedorn from Parker Fillmore relating to Edwin Arlington Robinson, a longtime resident of the colony.
Microfilm edition available for Colony Hall register (1923-1958) and Ernst Toch's string trio, opus 63, with his note (1956)
Microfilm produced from originals in the Manuscript Division.
Library of Congress Prints and Photographs Division.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Library of Congress Music Division.
Library of Congress Music Division.
Keywords: Allen, Hervey, -- 1889-1949.; Brodeur, Marie; Calder, Alexander, -- 1898-1976.; Colum, Mary; Colum, Padraic, -- 1881-1972.; Copland, Aaron, -- 1900-1990.; Fillmore, Louise Dutton; Fillmore, Parker, -- 1878-1944.; Frankel, Max, -- 1914-; Gross, Chaim, -- 1904-; Hagedorn, Hermann, -- 1882-1964.; Hale, Thomas Shaw; Heyward, DuBose, -- 1885-1940.; Isaacs, Lewis Montefiore, -- 1877-1944.; Kendall, George M; MacDowell, Edward, -- 1860-1908.; MacDowell, Marian, -- 1857-1956.; Moore, Marianne, -- 1887-1972.; Olsen, Tillie; Robinson, Edwin Arlington, -- 1869-1935.; Studin, Charles H; Sweeney, James Johnson, -- 1900-1986.; Talma, Louise, -- 1906-1996.; Untermeyer, Jean Starr, -- 1886-1970.; Wilder, Thornton, -- 1897-1975.; Artist colonies -- New Hampshire -- Peterborough; Artists; Authors; Musicians